Air travel across four time zones in college swimmers - O'Connor, P. J.; Morgan, W. P.; Koltyn, K. F.; Raglan, J. S.; Turner, J. G.; Kalin, N. H. (Journal of Applied Physiology, 1991)
The effects of travel in E-W and W-E directions across four time zones were measured in male and female college swimmers. A paced 200 yd swim at 90% of maximal velocity was performed pre- and post flights. Salivary cortisol, heart rate, sleep, and perceived exertion were measured. At rest on the day before and after travel blood pressure, heart rate, muscle soreness, and mood were evaluated. Significant mood changes and reductions in muscle soreness were observed after travel in both directions. No other major differences were evidenced. It was concluded that male and female college swimmers have similar responses to air travel and that such travel does not have negative physiological, perceptual, or affective consequences. Sleep alterations were influenced greater by W-E travel than E-W (large individual differences, fall asleep quicker, and increased sleep time). Implication: The authors caution against the common concerns about "jet lag" with athletes. However, the swimmers involved with this study were not "highly-tuned" or tapered nor were they dedicated athletes (their energies were shared between college and athletic responsibilities). They performed immediately after travel, before jet-lag symptoms had an opportunity to emerge. Individual variations in reactions to travel fatigue do occur, are greatly affected by the psychological state of the athlete, and also seem to be influenced by the purpose of the travel (e.g., reactions differ between holiday travel and Olympic Games travel). It is probable that larger time differences, particularly in the magnitude of one sleep-phase (8 hours), do affect performance.